2019
DOI: 10.25083/rbl/24.1/82.90
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age on sperm parameters in men with suspected infertility

Abstract: Male fertility has become a very discussed topic among researchers in the last years. With the latest environmental changes, use of genetically modified foods, lack of physical exercise, work overload and frequent burnouts, the number of men prone to infertility is continuously increasing. In this study, we aimed to evaluate the influence of age on the sperm quality in presumably infertile males. In this purpose, we have investigated a significant number of semen samples, by using macroscopic and microscopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Spermatozoa viability and progressive motility were decline with advancing age. This finding raises the possibility that the patient's age plays a role in male infertility and highlights the need for a deeper comprehension of the complex mechanisms and risks involved (Silea C, et al, 2019). In different study male partners of infertile couples aged 21-50 years did not significantly experience deterioration in semen quality with age in a cross-sectional observational research include 390 participants (Zabihullah M, et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…Spermatozoa viability and progressive motility were decline with advancing age. This finding raises the possibility that the patient's age plays a role in male infertility and highlights the need for a deeper comprehension of the complex mechanisms and risks involved (Silea C, et al, 2019). In different study male partners of infertile couples aged 21-50 years did not significantly experience deterioration in semen quality with age in a cross-sectional observational research include 390 participants (Zabihullah M, et al, 2023).…”
Section: Discussionmentioning
confidence: 95%
“…Pino et al reported that the risk of sperm damage increases with age while semen parameters decline (24). Silea et al stated sperm volume and motility decreased in infertile men over 40 compared to younger men (25). In the study of Kumar et al, the volume of semen fluid in men over 40 was 2.4 mL (26), and in the study of Omran et al, men over 40 had a volume of 2 mL and a concentration of 19.4*10 6 /mL (27).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a substantial association between body weights and diabetes mellitus, with the majority of T2DM patients being overweight or obese and having a higher chance of getting the disease. 13 Spermatogenesis and semen quality depends on the testosterone level and higher body weight lowering the testosterone level leads to poor semen quality. A review study indicate that obesity with diabetes decrease the semen quality and similar results were also observed in our study that group 2 participant's shows abnormal semen parameters as compared group 1 participants.…”
Section: Discussionmentioning
confidence: 99%